2013
DOI: 10.1111/cen.12280
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole stimulation in endometrial preparation for cryopreserved–thawed embryo transfer in women with polycystic ovarian syndrome: A pilot study

Abstract: Using letrozole stimulation in endometrial preparation for cryopreserved-thawed embryo transfer in patients with PCOS may be associated with better outcomes than using hormonal manipulation or hMG stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…4), MR (OR 1.02, 95 % CI: 0.60-1.74) and EMT (WMD 0.01, 95 % CI: − 1.69 to 1.70) (▶ Table 2). A statistically higher OPR (OR 4.50, 95 % CI: 1.62-12.48) was reported for the letrozole group in one study [24], while the other study reported a statistically lower LBR (OR 0.67, 95 % CI: 0.52-0.86) [25] (▶ Fig. 5, Table 2).…”
Section: Letrozole Versus Hmgmentioning
confidence: 80%
See 3 more Smart Citations
“…4), MR (OR 1.02, 95 % CI: 0.60-1.74) and EMT (WMD 0.01, 95 % CI: − 1.69 to 1.70) (▶ Table 2). A statistically higher OPR (OR 4.50, 95 % CI: 1.62-12.48) was reported for the letrozole group in one study [24], while the other study reported a statistically lower LBR (OR 0.67, 95 % CI: 0.52-0.86) [25] (▶ Fig. 5, Table 2).…”
Section: Letrozole Versus Hmgmentioning
confidence: 80%
“…It is also noteworthy that only two articles clearly stated that their study populations were PCOS patients [24,28], while the other articles did not clearly differentiate between patients. This meant that we were unable to perform subgroup analyses for women with or without a PCOS diagnosis.…”
Section: Letrozole Versus Acmentioning
confidence: 95%
See 2 more Smart Citations
“…[87][88][89][90] Letrozole FER requires fewer days of medication than medicated FER and small retrospective studies suggest at least equivalent clinical pregnancy rates. [91][92][93] However, more research is required.…”
Section: Ovarian Stimulation Cyclesmentioning
confidence: 99%